Organic two-dimensional material, preparation method thereof and solid super-lubricating material
The organic two-dimensional material prepared by conducting coupling reactions at the liquid-liquid interface solves the problem of easy decomposition of existing materials during friction, and realizes the preparation of high-performance ultraslip materials, which can significantly reduce friction and adhesion in mechanical equipment.
Patent Information
- Application Number
- CN202411955152.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing organic two-dimensional materials are easy to decompose during friction, making it difficult to meet the demand for high-performance ultra-slip materials in the mechanical field.
By mixing the porphyrin monomer, the organic boron reagent and the palladium catalyst in a non-polar organic solvent, an organic phase solution is formed, and alkaline substances are added to water to form an aqueous solution. The interface between the two-phase system undergoes coupling reactions to prepare an organic two-dimensional material bearing palladium element.
The prepared organic two-dimensional material has nanosheets, rods or clusters, which can directly enter the superlubrication interval without pre-running in the friction pair, significantly reducing friction and adhesion, and improving the service life and energy utilization of mechanical equipment.
Smart Images

Figure CN119751862A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of superlubricating materials, and specifically, to organic two-dimensional materials and preparation methods thereof, and solid superlubricating materials. Background Art
[0002] With the rapid development of industrial technology, friction and wear problems in the field of mechanical engineering are becoming increasingly severe. Friction not only leads to a large waste of energy, but also shortens the service life of mechanical equipment and increases its maintenance cost. It is reported that the energy consumed by friction each year accounts for more than a quarter of the energy provided by fossil fuels; in addition, the service life of mechanical equipment is short, and there are many low-end and high-energy-consuming equipment, which aggravates the waste of resources. Therefore, the development of new super-lubricating materials to reduce friction and wear is of great significance to improve energy utilization.
[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention
[0004] In the first aspect of the present application, the present application provides a method for preparing an organic two-dimensional material, comprising: adding a porphyrin monomer, an organic boron reagent, and a palladium catalyst to a non-polar organic solvent to obtain an organic phase solution; adding an alkaline substance to water to obtain an aqueous phase solution; transferring the organic phase solution to the aqueous phase solution to form a two-phase system; allowing the interface of the two-phase system to undergo a coupling reaction to obtain an organic two-dimensional material loaded with palladium elements; the reaction temperature of the coupling reaction is -2°C-10°C. Thus, under the action of the palladium catalyst and the alkaline substance, the porphyrin monomer and the organic boron reagent undergo a coupling reaction at the liquid-liquid interface formed by the organic phase and the aqueous phase, and the coupling reaction is carried out under low temperature conditions to obtain an organic two-dimensional material loaded with palladium metal.
[0005] In some embodiments, the structural formula of the porphyrin monomer includes: Any of the following:
[0006] Wherein, each R independently includes -Br, -I, -Cl, Any of the following:
[0007] A includes any one of -Br, -I, and -Cl;
[0008] M includes Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Any one of .
[0009] In some embodiments, the porphyrin monomer includes 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin, 5,10,15,20-tetrakis-(4-chlorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-fluorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromophenyl)porphyrin, 5,10,15,20-tetrakis-(4-methylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-ethylphenyl)porphyrin, 5,10,15,20- At least one of tetrakis-(4-isopropylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-iron(III) chloride, 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-cobalt(II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-nickel(II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-copper(II), and 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-zinc(II).
[0010] In some embodiments, the organoboron reagent includes at least one of 1,4-phenylenediboronic acid bis(pinacol) ester, 1,4-phenylenediboronic acid, 1,4-phenylenediboronic acid bis(neopentyl glycol) ester, 4,4'-biphenylenediboronic acid, and 4,4'-biphenylenediboronic acid bis(pinacol) ester.
[0011] In some embodiments, the palladium catalyst includes at least one of bistriphenylphosphine palladium dichloride, tetrakis(triphenylphosphine)palladium, bis(acetonitrile)palladium(II) chloride, 1,1'-bis(diphenylphosphino)ferrocenepalladium(II) dichloride, palladium acetate, palladium trifluoroacetate, and bis(acetylacetonate)palladium(II).
[0012] In some embodiments, the alkaline substance includes at least one of sodium carbonate, potassium carbonate, lithium carbonate, and cesium carbonate.
[0013] In some embodiments, the non-polar organic solvent includes at least one of benzene, carbon tetrachloride, hexane, isooctane, toluene, dichloromethane, cyclohexane, and petroleum ether.
[0014] In some embodiments, the molar ratio of the organic boron reagent to the porphyrin monomer is (1.5-2.5):1.
[0015] In some embodiments, in the organic phase solution, the concentration of the porphyrin monomer is 0.1 mmol / L-1 mmol / L.
[0016] In some embodiments, in the aqueous solution, the concentration of the alkaline substance is 1 mmol / L-10 mmol / L.
[0017] In some embodiments, the volume ratio of the non-polar organic solvent to the water is 1:(0.8-1.2).
[0018] In some embodiments, the molar ratio of the palladium catalyst to the porphyrin monomer is (0.01-1):1.
[0019] In some embodiments, when the reaction temperature of the coupling reaction is -2°C-5°C and the molar ratio of the palladium catalyst to the porphyrin monomer is (0.1-1):1, the organic two-dimensional material has a nanosheet structure.
[0020] In some embodiments, when the reaction temperature of the coupling reaction is -2°C-5°C and the molar ratio of the palladium catalyst to the porphyrin monomer is (0.01-0.1):1, the two-dimensional organic material has a rod-like structure.
[0021] In some embodiments, when the reaction temperature of the coupling reaction is 5-10° C. and the molar ratio of the palladium catalyst to the porphyrin monomer is (0.1-1):1, the organic two-dimensional material has a cluster structure.
[0022] In a second aspect of the present application, the present application provides an organic two-dimensional material prepared by the above method. Thus, the organic two-dimensional material of the present application has at least one of a nanosheet structure, a rod-like structure, and a cluster-like structure.
[0023] In a third aspect of the present application, the present application provides a solid superlubricating material, including an organic two-dimensional material prepared by the aforementioned method, or the aforementioned organic two-dimensional material. Thus, the homojunction friction pair composed of the solid superlubricating material of the present application can directly enter the superlubricating range without the need for a pre-running-in stage. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0025] Figure 1 This is a transmission electron microscope image of the organic two-dimensional material in Example 1.
[0026] Figure 2 This is a scanning electron microscope image of the friction surface of the lower pattern of the friction pair in Example 1.
[0027] Figure 3 This is a scanning electron microscope image of the friction surface of the friction pair in Example 1.
[0028] Figure 4 This is a transmission electron microscope image of the organic two-dimensional material in Example 2.
[0029] Figure 5This is a scanning electron microscope image of the friction surface of the lower pattern of the friction pair in Example 2.
[0030] Figure 6 This is a scanning electron microscope image of the friction surface of the friction pair in Example 2.
[0031] Figure 7 This is a transmission electron microscope image of the organic two-dimensional material in Example 3.
[0032] Figure 8 This is a scanning electron microscope image of the friction surface of the lower pattern of the friction pair in Example 3.
[0033] Fig. 9 This is a scanning electron microscope image of the friction surface of the friction pair in Example 3.
[0034] Fig.10 This is a transmission electron microscope image of the organic two-dimensional material in Example 4.
[0035] Fig.11 This is a scanning electron microscope image of the friction surface of the lower pattern of the friction pair in Example 4.
[0036] Fig.12 This is a scanning electron microscope image of the friction surface of the friction pair in Example 4.
[0037] Fig.13 This is the transmission electron microscope energy spectrum diagram of Example 1.
[0038] Fig.14 This is the transmission electron microscope energy spectrum diagram of Example 4.
[0039] Fig.15 This is a performance test diagram of Example 1, wherein: Fig.15 Figure (a) shows the variation of friction force with load. Fig.15 Figure (b) is the adhesion force distribution diagram. Fig.15 Figure (c) is the adhesion force histogram of 100 force curve tests.
[0040] Fig.16 This is a performance test diagram of Example 2, wherein: Fig.16 Figure (a) shows the variation of friction force with load. Fig.16 Figure (b) is the adhesion force distribution diagram. Fig.16 Figure (c) is the adhesion force histogram of 100 force curve tests.
[0041] Fig.17 This is a performance test diagram of Example 3, wherein: Fig.17 Figure (a) shows the variation of friction force with load. Fig.17 Figure (b) is the adhesion force distribution diagram. Fig.17Figure (c) is the adhesion force histogram of 100 force curve tests.
[0042] Fig.18 This is a performance test diagram of Example 4, wherein: Fig.18 Figure (a) shows the variation of friction force with load. Fig.18 Figure (b) is the adhesion force distribution diagram. Fig.18 Figure (c) is the adhesion force histogram of 100 force curve tests. DETAILED DESCRIPTION
[0043] Hereinafter, the organic two-dimensional material and its preparation method, and the solid superlubricant material implementation method of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0044] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be to include end values or not include end values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0048] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0049] Organic two-dimensional materials exhibit excellent mechanical properties due to their layered structure. At the same time, the interlayer forces of two-dimensional materials are extremely weak. These characteristics make two-dimensional materials theoretically ideal super-slippery materials. In addition, organic two-dimensional materials are easy to modify and adjust their structures, giving them functional regulation properties.
[0050] Currently, organic two-dimensional materials used in the field of lubrication can be divided into: two-dimensional structures formed by self-assembly of organic molecules through weak interactions such as van der Waals forces or hydrogen bonds; covalent organic frameworks formed by connecting organic elements through dynamic covalent bonds. However, the connection method of the layered structure of organic two-dimensional materials is weak bonding, which makes organic two-dimensional materials easy to decompose during friction and difficult to meet the needs of the rapid development of the mechanical field. Therefore, it is urgent to develop new organic two-dimensional materials to cope with the continuous advancement of mechanical technology.
[0051] In a first aspect of the present application, the present application provides a method for preparing an organic two-dimensional material, the method comprising:
[0052] S100, adding a porphyrin monomer, an organic boron reagent, and a palladium catalyst into a non-polar organic solvent to obtain an organic phase solution.
[0053] In some embodiments, the structural formula of the porphyrin monomer comprises: Any one of; wherein each R independently includes -Br, -I, -Cl, Any one of; A includes any one of -Br, -I, -Cl; M includes Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Any one of .
[0054] In some embodiments, the porphyrin monomer includes 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin, 5,10,15,20-tetrakis-(4-chlorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-fluorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromophenyl)porphyrin, 5,10,15,20-tetrakis-(4-methylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-ethylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-ethylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromophenyl)porphyrin, 5,10,15,20-tetrakis-(4-methylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-ethylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-fluorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromophenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromophenyl)porphyrin, 5,10,15,20-tetrakis-(4-methylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-ethylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromo ... -(4-isopropylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-iron(III) chloride, 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-cobalt(II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-nickel(II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-copper(II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-zinc(II).
[0055] Preferably, the porphyrin monomer includes 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin.
[0056] In some embodiments, the organoboron reagent includes at least one of 1,4-phenylenediboronic acid bis(pinacol) ester, 1,4-phenylenediboronic acid, 1,4-phenylenediboronic acid bis(neopentyl glycol) ester, 4,4'-biphenylenediboronic acid, and 4,4'-biphenylenediboronic acid bis(pinacol) ester.
[0057] Preferably, the organoboron reagent comprises 1,4-phenylenediboronic acid bis(pinacol) ester.
[0058] In some embodiments, the palladium catalyst includes at least one of bistriphenylphosphine palladium dichloride, tetrakis(triphenylphosphine)palladium, bis(acetonitrile)palladium(II) chloride, 1,1'-bis(diphenylphosphino)ferrocenepalladium(II) dichloride, palladium acetate, palladium trifluoroacetate, and bis(acetylacetonate)palladium(II).
[0059] Preferably, the palladium catalyst comprises tetrakis(triphenylphosphine)palladium.
[0060] In some embodiments, the molar ratio of the organoboron reagent to the porphyrin monomer is (1.5-2.5):1.
[0061] As an example, the molar ratio of the organoboron reagent to the porphyrin monomer may be 1.5:1, 1.7:1, 1.9:1, 2.1:1, 2.3:1 or 2.5:1.
[0062] In some embodiments, the molar ratio of the palladium catalyst to the porphyrin monomer is (0.01-1):1.
[0063] As an example, the molar ratio of the palladium catalyst to the porphyrin monomer can be 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1.
[0064] In some embodiments, the non-polar organic solvent includes at least one of benzene, carbon tetrachloride, hexane, isooctane, toluene, dichloromethane, cyclohexane, and petroleum ether.
[0065] In some embodiments, the concentration of the porphyrin monomer in the organic phase solution is 0.1 mmol / L-1 mmol / L.
[0066] As an example, in the organic phase solution, the concentration of the porphyrin monomer may be 0.1 mmol / L, 0.2 mmol / L, 0.4 mmol / L, 0.6 mmol / L, 0.8 mmol / L or 1 mmol / L.
[0067] S200, adding an alkaline substance into water to obtain an aqueous solution.
[0068] In some embodiments, the alkaline substance includes at least one of sodium carbonate, potassium carbonate, lithium carbonate, and cesium carbonate.
[0069] In some embodiments, the concentration of the alkaline substance in the aqueous solution is 1 mmol / L-10 mmol / L.
[0070] As an example, the concentration of the alkaline substance in the aqueous solution may be 1 mmol / L, 2 mmol / L, 4 mmol / L, 6 mmol / L, 8 mmol / L or 10 mmol / L.
[0071] S300, transferring the organic phase solution to the aqueous phase solution to form a two-phase system.
[0072] In some embodiments, the volume ratio of the non-polar organic solvent to water is 1:(0.8-1.2).
[0073] As an example, the volume ratio of the non-polar organic solvent to water may be 1:0.8, 1:0.9, 1:1.0, 1:1.1 or 1.2.
[0074] S400, allowing the interface of the two-phase system to undergo a coupling reaction to obtain an organic two-dimensional material loaded with palladium. Thus, under the action of a palladium catalyst and an alkaline substance, a porphyrin monomer and an organic boron reagent undergo a coupling reaction at a liquid-liquid interface formed by an organic phase and an aqueous phase to obtain an organic two-dimensional material loaded with palladium, wherein the organic two-dimensional material is composed of a plurality of porphyrin units, and each porphyrin unit is interconnected by a carbon-carbon (CC) bond.
[0075] In some embodiments, the reaction temperature of the coupling reaction is -2°C to 10°C, and the reaction time of the coupling reaction is 25 days to 35 days. Thus, the coupling reaction proceeds slowly under low temperature conditions to generate organic materials.
[0076] As an example, the reaction temperature of the coupling reaction can be -2°C, 0°C, 2°C, 4°C, 6°C, 8°C or 10°C.
[0077] As an example, the reaction time of the coupling reaction can be 25 days, 27 days, 29 days, 31 days, 33 days or 35 days.
[0078] In some embodiments, when the reaction temperature of the coupling reaction is -2°C-5°C and the molar ratio of the palladium catalyst to the porphyrin monomer is (0.1-1): 1, the organic two-dimensional material has a nanosheet structure. Thus, the reaction temperature of the coupling reaction is low, and the coupling reaction proceeds slowly, so that the porphyrin units can be effectively connected to each other through carbon-carbon (CC) bonds to form an organic two-dimensional material with a nanosheet structure, and the palladium nanoparticles evenly distributed on the surface of the nanosheet can reduce the surface energy of the nanosheet, thereby maintaining the sheet structure of the two-dimensional material.
[0079] In some embodiments, when the reaction temperature of the coupling reaction is -2°C-5°C and the molar ratio of the palladium catalyst to the porphyrin monomer is (0.01-0.1):1, the organic two-dimensional material has a rod-like structure. Thus, under the same reaction temperature conditions, when the content of the palladium catalyst is reduced, the generated nanoparticles are not sufficient to effectively reduce the surface energy of the large-area two-dimensional nanosheets, and the surface of the nanosheets is relatively smooth, and eventually curled to form a rod-like structure under the action of the surface energy. It is understandable that when the molar ratio of the palladium catalyst to the porphyrin monomer is 0.1:1, the organic two-dimensional material has both a nanosheet structure and a rod-like structure.
[0080] In some embodiments, when the reaction temperature of the coupling reaction is 5-10°C and the molar ratio of the palladium catalyst to the porphyrin monomer is (0.1-1): 1, the organic two-dimensional material has a cluster structure. Thus, under the same molar ratio of the palladium catalyst to the porphyrin monomer, the reaction temperature of the coupling reaction is increased, so that the reaction rate is accelerated. Although the evenly dispersed palladium nanoparticles can effectively reduce the surface energy of the nanosheet, the larger two-dimensional nanosheet structure will still produce wrinkles to overcome the increased surface energy during the growth process, thereby forming a cluster structure. It is understandable that when the reaction temperature of the coupling reaction is 5°C, the organic two-dimensional material has both a nanosheet structure and a cluster structure.
[0081] In some embodiments, after the coupling reaction is completed, ethanol is added to the two-phase system to obtain an emulsion, whereby ethanol can destroy the two-phase system of the organic phase and the aqueous phase, and the organic two-dimensional material is collected by centrifugation, further washed, and dispersed in ethanol.
[0082] In some embodiments, the volume ratio of ethanol to the non-polar organic solvent is (1-2):1.
[0083] As an example, the volume ratio of ethanol to the non-polar organic solvent can be 1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1.
[0084] In some embodiments, the emulsion is centrifuged to obtain the organic two-dimensional material, wherein the rotation speed of the centrifugation is 5000 rpm-1200 rpm, and the time of the centrifugation is 5 min-20 min.
[0085] As an example, the rotation speed of the centrifugal treatment can be 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm or 1200 rpm.
[0086] As an example, the centrifugation time may be 5 min, 10 min, 15 min or 20 min.
[0087] In some embodiments, the coupling reaction needs to be carried out under a protective atmosphere, which may include argon and nitrogen.
[0088] In a second aspect of the present application, the present application provides an organic two-dimensional material prepared by the above method. Thus, the organic two-dimensional material of the present application has at least one of a nanosheet structure, a rod-like structure, and a cluster-like structure.
[0089] In a third aspect of the present application, the present application provides a solid superlubricating material, including an organic two-dimensional material prepared by the aforementioned method, or the aforementioned organic two-dimensional material. Thus, the homojunction friction pair composed of the solid superlubricating material of the present application can directly enter the superlubricating range without the need for a pre-running-in stage.
[0090] In some embodiments, in the solid superlubricating material, the organic two-dimensional material needs to be made into an organic two-dimensional material layer for use, and the method for preparing the organic two-dimensional material layer includes:
[0091] S100, adding an organic two-dimensional material into a dispersant to obtain a dispersed solution.
[0092] In some embodiments, the dispersant includes ethanol. Thus, the organic two-dimensional material can be effectively dispersed to obtain a more uniform dispersed solution.
[0093] In some embodiments, the concentration of the organic two-dimensional material in the dispersed solution is 0.1 mg / mL-1 mg / mL. Thus, a uniform dispersed solution can be further obtained.
[0094] As an example, in the dispersed solution, the concentration of the organic two-dimensional material can be 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL or 1 mg / mL.
[0095] S200, performing ultrasonic dispersion treatment on the dispersed solution; the ultrasonic power of the ultrasonic dispersion treatment is 350W-960W, and the ultrasonic time of the ultrasonic dispersion treatment is 5h-10h. Thus, the agglomerates of the organic two-dimensional material can be further dispersed, and the uniformity of the organic two-dimensional material in the dispersed solution can be improved.
[0096] As an example, the ultrasonic power of the ultrasonic dispersion treatment may be 350 W, 450 W, 550 W, 650 W, 750 W, 850 W, 950 W, or 960 W.
[0097] As an example, the ultrasonic dispersion treatment may be carried out for 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0098] S300, transferring the dispersed solution into a reverse phase solvent to obtain a two-dimensional material layer, wherein the two-dimensional material layer has a high degree of orientation.
[0099] Thus, the organic two-dimensional material can be transferred from the dispersed solution to the surface of the reverse solvent, so that the organic two-dimensional material can be effectively oriented at the reverse solvent-air interface, thereby forming a highly oriented two-dimensional material layer.
[0100] In some embodiments, the reverse phase solvent includes water, so that ethanol can be dissolved in water, and the organic two-dimensional material can be evenly spread on the surface of the water to form a highly oriented two-dimensional material layer.
[0101] In some embodiments, the volume ratio of the dispersion solution to the reversed-phase solvent is (0.01-0.1): 1. Thus, the amount of the organic two-dimensional material transferred to the reversed-phase solvent can be precisely controlled.
[0102] As an example, the volume ratio of the dispersion solution to the reverse phase solvent may be 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1 or 0.1:1.
[0103] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0104] Example 1
[0105] (1) Preparation of organic two-dimensional materials
[0106] S100, adding 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin and 1,4-phenylenediboronic acid bis(pinacol) ester to toluene to obtain a toluene solution, wherein the concentration of 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin in the toluene solution is 0.5 mmol / L, and the molar ratio of 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin to 1,4-phenylenediboronic acid bis(pinacol) ester is 1:2;
[0107] Under argon protection, tetrakis(triphenylphosphine)palladium was added to the toluene solution, and the molar ratio of tetrakis(triphenylphosphine)palladium to 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin was 0.5:1.
[0108] S200, adding potassium carbonate into deoxygenated water to obtain an aqueous solution, wherein the concentration of potassium carbonate in the aqueous solution is 5 mmol / L, and the volumes of toluene and deoxygenated water are the same.
[0109] S300. Under argon protection, the toluene solution is transferred into the aqueous solution to form a two-phase system.
[0110] S400. Allow a coupling reaction to occur at the interface of the two-phase system. The reaction temperature of the coupling reaction is 2°C. After 30 days of reaction, ethanol (the volume ratio of ethanol to toluene is 1:1) is added to the two-phase system to obtain an emulsion. The emulsion is centrifuged at 8000 rpm for 10 min to collect the solid product. The obtained solid product is washed twice with ethanol and then centrifuged again to obtain an organic two-dimensional material.
[0111] In this embodiment, the reaction formula for generating an organic two-dimensional material from 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin and 1,4-phenyldiboronic acid bis(pinacol) ester is:
[0112]
[0113] Among them, organic two-dimensional materials represent The repeating units of the monomers are connected by connect.
[0114] (2) Preparation of two-dimensional material layer
[0115] S100, dispersing the organic two-dimensional material in ethanol to obtain a dispersed solution containing the organic two-dimensional material; wherein the concentration of the organic two-dimensional material in the dispersed solution is 0.5 mg / mL.
[0116] S200, performing ultrasonic dispersion treatment on the dispersed solution; wherein the ultrasonic power of the ultrasonic dispersion treatment is 550W, and the ultrasonic time of the ultrasonic dispersion treatment is 6h;
[0117] S300, then use a pipette to absorb the dispersed solution, and then add the dispersed solution dropwise into an open container filled with pure water. The water surface will be covered with the organic two-dimensional material. At this time, a highly oriented organic two-dimensional material layer is formed; the volume ratio of the dispersed solution to water is 0.05:1.
[0118] (3) Preparation of the lower sample of the friction pair
[0119] The lower sample used in this embodiment is a thin plate.
[0120] Use a four-claw clamp or a vacuum suction cup to fix the back of the lower sample of the friction pair, press the lower sample vertically to contact the organic two-dimensional material layer floating on the water surface; then quickly lift the lower sample, and the organic two-dimensional material layer will adhere to the friction surface of the lower sample; after the attached lower sample is air-dried on the clean bench for 1 minute, it is immediately immersed vertically in another open container filled with pure water for 30 seconds; finally, the lower sample is air-dried again in the clean bench for 1 minute. The above steps constitute a complete process of transferring the organic two-dimensional material layer to the lower sample, and the transfer step is repeated 30 times to obtain a lower sample covered with multiple layers of organic two-dimensional materials.
[0121] (4) Preparation of the friction pair pattern
[0122] The upper sample used in this embodiment is a silica spherical probe, and an atomic force microscope is used in its preparation process. The atomic force microscope can not only serve as a fixture for the upper sample, but also can accurately control the movement of the upper sample in the vertical direction.
[0123] The contact mode of the atomic force microscope is turned on, and the silica spherical probe is gradually lowered; after the atomic force microscope shows a signal that the silica spherical probe has touched the water surface, it is kept for 1 minute; then the silica spherical probe is lifted from the water surface and dried in the air for 5 minutes, and the organic two-dimensional material layer will adhere to the rubbing surface of the upper pattern. The above steps constitute a complete process of transferring the organic two-dimensional material layer to the upper pattern, and the transfer step is repeated 20 times to obtain the upper pattern covered with multiple layers of organic two-dimensional materials.
[0124] Example 2
[0125] The difference between Example 2 and Example 1 is that the reaction temperature of the coupling reaction is 7°C.
[0126] Example 3
[0127] The difference between Example 3 and Example 1 is that the molar ratio of tetrakis(triphenylphosphine)palladium to 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin is 0.05:1.
[0128] Example 4
[0129] The difference between Example 4 and Example 1 is that the porphyrin monomer is 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-copper (II).
[0130] Structural characterization
[0131] 1. The organic two-dimensional materials in Examples 1 to 4 are scanned by a transmission electron microscope, and the friction surfaces of the lower pattern of the friction pair and the friction surfaces of the upper pattern of the friction pair are scanned by a scanning electron microscope.
[0132] The transmission electron microscope image of the organic two-dimensional material in Example 1 and the scanning electron microscope images of the friction surface of the lower pattern of the friction pair and the friction surface of the upper pattern of the friction pair are shown as follows: Figure 1-Figure 3 As shown. Figure 1-Figure 3 , the nanosheet structure can be observed.
[0133] The transmission electron microscope image of the organic two-dimensional material in Example 2 and the scanning electron microscope images of the friction surface of the lower pattern of the friction pair and the friction surface of the upper pattern of the friction pair are shown as follows: Figure 4-Figure 6 As shown. Figure 4-Figure 6 , a cluster-like structure can be observed.
[0134] The transmission electron microscope image of the organic two-dimensional material in Example 3 and the scanning electron microscope images of the friction surface of the lower pattern of the friction pair and the friction surface of the upper pattern of the friction pair are shown in FIG. Figure 7-Figure 9 As shown. Figure 7-Figure 9 , a rod-like structure can be observed.
[0135] The transmission electron microscope image of the organic two-dimensional material in Example 4 and the scanning electron microscope images of the friction surface of the lower pattern of the friction pair and the friction surface of the upper pattern of the friction pair are shown as follows: Figure 10-12 As shown. Figure 10-12 , the nanosheet structure can be observed.
[0136] 2. Perform element detection on the organic two-dimensional materials in Example 1 and Example 4.
[0137] The transmission electron microscope energy spectrum (EDS) of Example 1 is as follows: Fig.13 shown. Fig.13 It can be observed that the organic two-dimensional material is loaded with palladium. On the friction interface of the homojunction friction pair, the palladium particles act as nanobearings, which helps to enhance the lubrication effect and reduce friction; during the contact process of the friction pair, the heterogeneous interface formed by the palladium particles and the organic two-dimensional material reduces the common contact between the two-dimensional crystal planes, thereby reducing the possibility of atomic-level bite.
[0138] The EDS diagram of Example 4 is as follows: Fig.14 shown. Fig.14 Organic two-dimensional materials can be observed to have copper elements.
[0139] Performance Testing
[0140] The upper and lower friction pair patterns of the friction pair of Example 1 constitute a homojunction friction pair 1, the upper and lower friction pair patterns of Example 2 constitute a homojunction friction pair 2, the upper and lower friction pair patterns of Example 3 constitute a homojunction friction pair 3, and the upper and lower friction pair patterns of Example 4 constitute a homojunction friction pair 4. Microscopic friction experiments were conducted on homojunction friction pairs 1-4, that is, the friction surface of the upper friction pair pattern and the friction surface of the lower friction pair pattern (3 μm) 2 ×3μm 2 ) relative sliding, the experimental results of Example 1-Example 4 are as follows Figure 15-18 shown.
[0141] For Example 1, Fig.15 Figure (b) is an adhesion force distribution diagram, which is used to show the adhesion force distribution measured at different positions. The depth of its color can intuitively show the spatial distribution of adhesion force. Fig.15 (c) is an adhesion force histogram of 100 force curve tests. It is calculated that the average adhesion force of Example 1 is 19 nN. Fig.15 (a) is a graph showing the variation of friction force with load in Example 1. The friction force and load data are linearly fitted, and the slope obtained represents the friction coefficient, and the vertical axis intercept represents the friction force under zero load conditions. The friction coefficient of Example 1 is 0.0046, and the zero load friction is 48.5 pN. At the same time, the shear adhesion force is 10.5 nN according to the ratio of the vertical axis intercept to the friction coefficient.
[0142] For Example 2, Fig.16 Figure (b) is the adhesion force distribution diagram. Fig.16 (c) is an adhesion force histogram of 100 force curve tests. It is calculated that the average adhesion force of Example 2 is 24.9 nN. Fig.16(a) is a graph showing the variation of friction force with load in Example 2. Linear fitting of the friction force and load data shows that the friction coefficient of Example 2 is 0.0057, the zero load friction is 113.6 pN, and the shear adhesion is 19.9 nN.
[0143] For Example 3, Fig.17 Figure (b) is the adhesion force distribution diagram. Fig.17 (c) is an adhesion force histogram of 100 force curve tests, and it is calculated that the average adhesion force of Example 3 is 19.2 nN. Fig.17 (a) is a graph showing the variation of friction force with load in Example 3. Linear fitting of the friction force and load data shows that the friction coefficient of Example 3 is 0.0018, the zero load friction is 32.5 pN, and the shear adhesion is 17.5 nN.
[0144] For Example 4, Fig.18 Figure (b) is the adhesion force distribution diagram. Fig.18 (c) is an adhesion force histogram of 100 force curve tests. It is calculated that the average adhesion force of Example 4 is 20 nN. Fig.18 (a) is a graph showing the variation of friction force with load in Example 4. Linear fitting of the friction force and load data shows that the friction coefficient of Example 4 is 0.0026, the zero load friction is 45.4 pN, and the shear adhesion is 17.5 nN.
[0145] From the above results, it can be seen that the adhesion between the friction pairs of Examples 1 to 4 is extremely low, which is due to the extremely weak interlayer interaction of the organic two-dimensional material, and its homojunction friction pair can directly enter the superlubrication range without the need for a pre-running-in stage. Among them, Example 3 has the best anti-adhesion and lubrication properties, which is due to its smooth surface and small contact area.
[0146] Comparative Example 1
[0147] The difference between Comparative Example 1 and Example 1 is that the reaction temperature of the coupling reaction is 15°C.
[0148] The friction coefficient of the homojunction friction pair composed of the upper and lower friction pairs of comparative example 1 is 0.032, and the zero-load friction is 383 pN. This is because the temperature of the coupling reaction is too high, resulting in too fast reaction, and the excessive agglomeration of the product will form a large block of material, which is difficult to play a lubricating role, but will cause abrasive wear.
[0149] Comparative Example 2
[0150] The difference between Comparative Example 2 and Example 1 is that the reaction temperature of the coupling reaction is -5°C.
[0151] The friction coefficient of the homojunction friction pair composed of the upper and lower friction pairs of comparative example 2 is 0.013, and the zero-load friction is 1948 pN. This is because the temperature of the coupling reaction is too low, the reaction proceeds slowly, it is difficult to obtain nanosheets with large lateral dimensions, and the lubrication effect at the friction interface is weakened.
[0152] Comparative Example 3
[0153] The difference between Comparative Example 3 and Example 1 is that the molar ratio of tetrakis(triphenylphosphine)palladium to 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin is 1.2:1.
[0154] The friction coefficient of the homojunction friction pair composed of the upper and lower friction pairs of comparative example 3 is 0.021, and the zero-load friction is 725 pN. This is because the excessive catalyst content causes large catalyst particles to remain on the surface of the organic two-dimensional material, greatly increasing the surface roughness of the organic two-dimensional material.
[0155] Comparative Example 4
[0156] The difference between Comparative Example 4 and Example 1 is that the organic two-dimensional nanosheets of Example 1 are washed with a 0.1 mol / L hydrochloric acid solution to remove the palladium particles.
[0157] The friction coefficient of the homojunction friction pair composed of the upper and lower friction pairs of comparative example 4 is 0.0058, and the zero-load friction is 1137 pN. This is because the contact crystal planes of the organic two-dimensional material have commensurate contact during the sliding process, resulting in atomic-level bite, thereby increasing the friction force.
[0158] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing an organic two-dimensional material, characterized in that: include: adding a porphyrin monomer, an organic boron reagent, and a palladium catalyst into a non-polar organic solvent to obtain an organic phase solution; Adding an alkaline substance into water to obtain an aqueous solution; transferring the organic phase solution into the aqueous phase solution to form a two-phase system; A coupling reaction is performed at the interface of the two-phase system to obtain an organic two-dimensional material loaded with palladium element; the reaction temperature of the coupling reaction is -2°C-10°C.
2. The method according to claim 1, characterized in that The structural formula of the porphyrin monomer includes: Any of the following: Wherein, each R independently includes -Br, -I, -Cl, Any of the following: A includes any one of -Br, -I, and -Cl; M includes Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Any one of .
3. The method according to claim 2, characterized in that The porphyrin monomers include 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin, 5,10,15,20-tetrakis-(4-chlorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-fluorophenyl)porphyrin, 5,10,15,20-tetrakis-(4-bromophenyl)porphyrin, 5,10,15,20-tetrakis-(4-methylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-ethylphenyl)porphyrin, 5,10,15,20-tetrakis-(4 -isopropylphenyl)porphyrin, 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-iron (III) chloride, 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-cobalt (II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-nickel (II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-copper (II), 5,10,15,20-tetrakis-(4-iodophenyl)porphyrin-zinc (II).
4. The method according to claim 1, characterized in that The organic boron reagent includes at least one of 1,4-phenylenediboronic acid bis(pinacol) ester, 1,4-phenylenediboronic acid, 1,4-phenylenediboronic acid bis(neopentyl glycol) ester, 4,4'-biphenylenediboronic acid, and 4,4'-biphenylenediboronic acid bis(pinacol) ester; and / or, The palladium catalyst includes at least one of bistriphenylphosphine palladium dichloride, tetrakis(triphenylphosphine)palladium, bis(acetonitrile)palladium chloride(II), 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride(II), palladium acetate, palladium trifluoroacetate, and bis(acetylacetonate)palladium(II).
5. The method according to claim 1, characterized in that The alkaline substance includes at least one of sodium carbonate, potassium carbonate, lithium carbonate and cesium carbonate; and / or, The non-polar organic solvent includes at least one of benzene, carbon tetrachloride, hexane, isooctane, toluene, dichloromethane, cyclohexane and petroleum ether.
6. The method according to claim 1, characterized in that The molar ratio of the organic boron reagent to the porphyrin monomer is (1.5-2.5):1; and / or, The molar ratio of the palladium catalyst to the porphyrin monomer is (0.01-1):1; and / or, In the organic phase solution, the concentration of the porphyrin monomer is 0.1 mmol / L-1 mmol / L; and / or, In the aqueous solution, the concentration of the alkaline substance is 1 mmol / L-10 mmol / L; and / or, The volume ratio of the non-polar organic solvent to the water is 1:(0.8-1.2).
7. The method according to claim 6, characterized in that When the reaction temperature of the coupling reaction is -2°C-5°C: The molar ratio of the palladium catalyst to the porphyrin monomer is (0.1-1):1, and the organic two-dimensional material has a nanosheet structure; and / or, The molar ratio of the palladium catalyst to the porphyrin monomer is (0.01-0.1):1, and the two-dimensional organic material has a rod-like structure.
8. The method according to claim 6, characterized in that When the reaction temperature of the coupling reaction is 5-10° C., the molar ratio of the palladium catalyst to the porphyrin monomer is (0.1-1):1, and the organic two-dimensional material has a cluster structure.
9. An organic two-dimensional material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. A solid superlubricating material, characterized in that: Including the organic two-dimensional material according to claim 9, or the organic two-dimensional material prepared by the method according to any one of claims 1-8.
Citation Information
Patent Citations
Micro-nano reactor based on phthalocyanine bridging methylation cyclodextrin and preparation of micro-nano reactor
CN103446969A
Solid-phase microextraction coating based on metalloporphyrin microporous polymer, and preparation and application thereof
CN107126941A
Method for carbon-carbon coupling using palladium catalyst composition
JP2005060335A